FORECASTING OF PARAMETRIC RELIABILITY OF HYDRAULIC STEERING BOOSTER OF MOBILE MACHINE - G. A. Mrochek; V. P. Tarasik; T. V. Mrochek (Наука и техника)
An algorithm for forecasting parametric reliability of  hydraulic steering booster during its operation has been developed in the paper. Regression models of output characteristics allowing to determine a reserve  resource for two important devices of the steering booster, namely: flow regulator and control valve have been obtained in the paper. Stochastic characteristics of failure distribution  that may be used while estimating parameters of steering booster reliability are given in the paper.